2015
DOI: 10.1038/bmt.2015.275
|View full text |Cite
|
Sign up to set email alerts
|

The safety and feasibility of probiotics in children and adolescents undergoing hematopoietic cell transplantation

Abstract: Hematopoietic cell transplantation (HCT) has become a standard treatment for many adult and pediatric conditions. Emerging evidence suggests that perturbations in the microbiota diversity increase recipients' susceptibilities to gut-mediated conditions such as diarrhea, infection and acute GvHD. Probiotics preserve the microbiota and may minimize the risk of developing a gutmediated condition; however, their safety has not been evaluated in the setting of HCT. We evaluated the safety and feasibility of the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(93 citation statements)
references
References 42 publications
1
86
0
6
Order By: Relevance
“…53, 94 Assessment of the safety of Lactobacillus administration to human HCT patients has shown promising results 95 but the impact on GVHD development has yet to be reported. Although the use of these treatments seem promising, future studies should clarify both the safety and efficiency for these therapies in the clinical setting.…”
Section: Nutrition and Gvhdmentioning
confidence: 99%
“…53, 94 Assessment of the safety of Lactobacillus administration to human HCT patients has shown promising results 95 but the impact on GVHD development has yet to be reported. Although the use of these treatments seem promising, future studies should clarify both the safety and efficiency for these therapies in the clinical setting.…”
Section: Nutrition and Gvhdmentioning
confidence: 99%
“…Second, correcting intestinal dysbiosis is critically important, although only a report [34] demonstrated that intestinal dysbiosis was associated with subsequent bacteremia. Prophylactic administration of Lactobacillus plantarum (probiotics) has proven to be safe and feasible in children and adolescents undergoing allo-HSCT [35], whereas another randomized clinical trial using Lactobacillus rhamnosus GG failed to alter the intestinal microbiome and GVHD incidence [36]. In addition, several case reports have suggested that the probiotic itself caused septicemia in highly immunocompromised HSCT recipients [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Safety and feasibility were demonstrated and, most of all, no cases of L. Plantarum bacteremia were observed. 85 FMT consists of the introduction of a fecal suspension derived from a healthy donor. It was successfully in a patient with recurrent Clostridium difficile-associated disease.…”
Section: Future Perspectivesmentioning
confidence: 99%